2016
DOI: 10.1080/03719553.2016.1166565
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of flame front speed on iron ore sintering conditions

Abstract: It is well established that flame front speed is an important factor influencing sinter productivity, sinter quality and fuel rate. In this work, the effect of suction, coke addition and mix moisture on flame front speed was studied in a pilot-scale sinter pot and also using a recently developed theoretical model. Airflow through the bed has a large influence on flame front speed. It was found that increasing sintering airflow rate will lead to increased flame front speed, but the increases become smaller at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Increasing the coke addition rate was observed to increase the peak bed temperature and time at temperature, consistent with past observations [10]. The increase in coke rate results in increases in the heat generated.…”
Section: Peak Bed Temperaturesupporting
confidence: 91%
See 1 more Smart Citation
“…Increasing the coke addition rate was observed to increase the peak bed temperature and time at temperature, consistent with past observations [10]. The increase in coke rate results in increases in the heat generated.…”
Section: Peak Bed Temperaturesupporting
confidence: 91%
“…The temperature and thermal history of sinter can be controlled with the addition of coke breeze and adjustment of the sinter draft pressure [1]. Previous modelling and sinter pot tests have demonstrated that with an increase in coke rate there is an increase in the sinter peak bed temperature and time at temperature [10], and with an increase in the draft pressure there is a decrease in the sinter peak bed temperature and time at temperature.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is found that the maximum exhaust-gas temperature is proliferated dramatically with external mechanical pressure increased from 0 Pa to 6242 Pa, while that rises slightly as the external mechanical pressure continues to reach 7803 Pa. Furthermore, the sintering time is prolonged constantly with external mechanical pressure and the relevant vertical sintering speed is continuously lowered, as shown in Figure 5b due to the densification of the loose sinter from the surface to the central layer under external mechanical pressure [41]. This is harmful to the productivity of the product sinter to some extent.…”
Section: Thermodynamic and Kinetic Conditions During Sinteringmentioning
confidence: 93%
“…Thus, the proper increase of external mechanical pressure (0-6242 Pa) is conducive to the significant improvement of sintering performance of limonitic laterite. However, as the external mechanical pressure exceeds the appropriate value, the permeability of the sinter bed is overly lowered because of the excessive densification of the sinter, resulting in rather low vertical sintering speed, and then the deterioration of the sintering performance [41]. Hence, the optimum external mechanical pressure is recommended at 6242 Pa.…”
Section: Effect Of External Mechanical Pressure On Sintering Performancementioning
confidence: 99%
“…Results from carefully controlled tests on a pilot-scale sinter pot were used to validate the 2D sintering model. All of the experimental results have been discussed in earlier publications. ,,, The dimension of the cylindrical sinter pot is 600 mm in height and 330 mm in diameter, as shown in Figure . The inner pot wall was made of stainless steel.…”
Section: Methodsmentioning
confidence: 99%